about astigmatism in Iraqis prevalence and patterns of Astigmatic refractive errors in a sample of normal Iraqi adults - Mehdy, IMAD SALIH (Karbala Journal of Medicine, 2020)
Abstract: Background Astigmatism is an important clinical and public health issue, it is one of major refractive errors affecting population, persistent astigmatism will cause ametropia and reduced visual acuity by prohibiting the formation of a clear image on the retina which will result in poor work performance.6,7 Purpose To determine the prevalence of astigmatism, and the astigmatic axis. To investigate the differences in types and magnitude of astigmatism among different age groups and gender in a sample of normal Iraqi adults.